Virulent Mycobacterium tuberculosis Strains Evade Apoptosis of Infected Alveolar Macrophages - Keane, Joseph (My University, 2000)
Human alveolar macrophages (AMφ) undergo apoptosis following infection with Mycobacterium tuberculosis in vitro. Apoptosis of cells infected with intracellular pathogens may benefit the host by eliminating a supportive environment for bacterial growth.The present study compared AMφ apoptosis following infection by M. tuberculosis complex strains of differing virulence and by Mycobacterium kansasii. A virulent or attenuated bacilli (M. tuberculosis H37Ra, Mycobacterium bovis bacillus Calmette-Guerin, and M. kansasii) induced significantly more AMφ apoptosis than virulent strains (M. tuberculosis H37Rv, Erdman, M. tuberculosis clinical isolate BMC 96.1, and M. bovis wild type). Increased apoptosis was not due to greater intracellular bacterial replication because virulent strains grew more rapidly in AMφ than attenuated strains despite causing less apoptosis. These findings suggest the existence of mycobacterial virulence determinants that modulate the apoptotic response of AMφ to intracellular infection and support the hypothesis that macrophage apoptosis contributes to innate host defense in tuberculosis.
Keywords: Human alveolar macrophages (AMφ); Apoptosis; Tuberculosis